The rights to legal counsel in Ethiopia: Evidence obtained in absence of legal counsel - Lamessa Gudeta Guder (Journal of Management and Science, 2023)
The Right to legal Counsel is a basic right of human rights as provided under different international, regional and National instruments as crucial elements of rights to fair trial. The presence of counsel serves multiple purposes, including the Redress of the power imbalance between the authorities and the detained (particularly in terms of knowledge of the law), deterrence of torture and other ill-treatment capacity to address arbitrary or improperly justified detention, and ability to provide an alternative record of interviews to ensure the integrity of any evidence gathered. In many Jurisdictions the confession obtained in absence of lawyers are inadmissible as criminal evidences.In Ethiopia, the Defendant/accused person to assist by legal counsel is a constitutional rights givens by our laws at National level and at different Regional state level. However practically what we have seen in area of our courts, police custody, prison the place where this right has been implemented is allegedly different from what is said by law. In some circumstance, even the law by itself seems to be incompatible with practical application of this right. Such disparity and gap of the law and the practice regarding this defendant right has great impact on the fair trial. The inadmissibility of evidence obtained in absence of legal counsel did not provided by Ethiopian laws. Even when the detained/arrested/ person can get the legal counsel ( at what time?) by itself is not clear.This in turn begs different question among legal professionals regarding the admissibility or inadmissibility of evidence obtained in absence of legal counsel. This article try to identify the position of our laws, consult different jurisprudences of the other model country and gives clue for the criminal lawyers and legal professionals as to the respection of the rights to legal counsel as basic fair trial. And inadmissibility of any evidence obtained in absence of legal counsel since it has irretrievable effects on the defense rights.